Missed Nursing Care in the Perinatal Setting. Issue 4 (July 2016) - Simpson, Kathleen Rice
Abstract : Missed nursing care is a concept that has been studied widely over the past few years, but not in maternity or neonatal units. For the purposes of measurement, missed care has been conceptualized by researchers as nursing care that is not done in a timely manner, not done as completely as needed, or not done at all (i.e., delayed, unfinished, or missed care). Missed nursing care is worthy of study in the perinatal setting because we all know when nurses are too busy, things can get missed.